2002
DOI: 10.1121/1.4779792
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations in the whistles of spinner dolphins (Stenellalongirostris)

Abstract: In order to better understand the reasons for geographic variations in the whistles of spinner dolphins (Stenella longirostris), recordings made in the Eastern Tropical Pacific will be compared to those recorded off Midway Atoll, Northwestern Hawai’ian Islands, the island of O’ahu, main Hawai’ian Islands, and Mo’orea, French Polynesia using discriminant function analysis. The values of 10 variables were extracted from the fundamental frequency (contour) of each whistle selected for analysis (begin, end, maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…It is also known that spinner dolphin whistles can vary geographically ͑Bazúa- Durán and Au, 2001;Bazúa-Durán et al, 2003;Bazúa-Durán and Au, 2004͒, as it was already observed for bottlenose dolphins, Tursiops truncatus ͑Wang et al, 1995b;Jones and Sayigh, 2002͒, and for the estuarine dolphin, Sotalia guianensis ͑Azevedo and Van Sluys, 2005͒. Nevertheless, the factors influencing this observed geographic variation are still unclear, once the pattern found for spinner dolphins does not follow exactly those observed for the other two species.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is also known that spinner dolphin whistles can vary geographically ͑Bazúa- Durán and Au, 2001;Bazúa-Durán et al, 2003;Bazúa-Durán and Au, 2004͒, as it was already observed for bottlenose dolphins, Tursiops truncatus ͑Wang et al, 1995b;Jones and Sayigh, 2002͒, and for the estuarine dolphin, Sotalia guianensis ͑Azevedo and Van Sluys, 2005͒. Nevertheless, the factors influencing this observed geographic variation are still unclear, once the pattern found for spinner dolphins does not follow exactly those observed for the other two species.…”
Section: Introductionmentioning
confidence: 81%
“…O'ahu groups were very similar to TEP and Mo'orea groups, suggesting that there are no differences between oceanic and coastal spinner dolphin whistles. Bazúa-Durán and Au ͑2002͒ claimed that the distinctiveness of Midway whistles could be due to the stability of the spinner dolphins in that area, and that the geographic differences found may not occur solely due to geographic isolation, and that other factors, such as fluidity of the spinner dolphin groups may be also affecting this variation ͑Bazúa- Durán et al, 2003͒. In order to evaluate the variability of spinner dolphin whistles from the Fernando de Noronha Archipelago off Brazil ͑considered as S. longirostris longirostris͒, we conducted a series of quali-and quantitative analyses, which are presented here. No other study on this topic has been done in the Southwestern Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The following standard whistle parameters (Baz ua-Dur an and Au, 2004;May-Collado and Wartzok, 2008) were measured: starting frequency (SF), ending frequency (EF), minimum frequency (MinF), maximum frequency (MaxF), delta frequency (DF), peak frequency (PF), duration (s), number of inflection points, and number of harmonics.…”
Section: Methodsmentioning
confidence: 99%
“…Thus the data from Hong Kong cannot be extrapolated into the other regions. In addition, microgeographic and/or macrogeographic variations in dolphin whistles were frequently observed (Wang et al, 1995a;Baz ua-Dur an and Au, 2004;Azevedo and Sluys, 2005;Morisaka et al, 2005b;Hawkins, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Whistles are frequencymodulated narrowband sounds with the function including, but not limited to, communication between conspecifics (Janik, 2000), group organization, and cohesion (Janik and Slater, 1999;Janik, 2000;Janik et al, 2006). They have been widely adopted for species characterization (Baz uaDur an and Au, 2002;Azevedo et al, 2007;May-Collado and Wartzok, 2009) and for microgeographic and macrogeographic comparisons among different populations of the same species (Wang et al, 1995a;Baz ua-Dur an and Au, 2004;Azevedo and Sluys, 2005;Morisaka et al, 2005b;Hawkins, 2010) and among different species (Wang et al, 1995b;Wang et al, 2001;Oswald et al, 2003).…”
Section: Introductionmentioning
confidence: 99%